A Gap Between Willingness and Uptake: Findings From Mixed Methods Research on HIV Prevention Among Black and Latina Transgender Women. (1st October 2019) - Poteat, Tonia; Wirtz, Andrea; Malik, Mannat; Cooney, Erin; Cannon, Christopher; Hardy, W. David; Arrington-Sanders, Renata; Lujan, Maren; Yamanis, Thespina
Abstract : Background: Black and Latina transgender women (BLTW) face significant HIV disparities with estimated HIV prevalence up to 50% and annual incidence rates as high as 2.8 per 100 person-years. However, few studies have evaluated the acceptability and uptake of high-impact HIV prevention interventions among BLTW. Setting: Data collection took place in Baltimore, MD and Washington, DC from May 2015 to May 2017. Methods: This mixed methods study included quantitative interviewer-administered surveys, key informant interviews, and focus group discussions. Rapid HIV testing followed each survey. Logistic regression models tested associations between legal gender affirmation (ie, desired name and gender marker on identity documents), transgender pride, history of exchange sex, HIV risk perception, and willingness to take pre-exposure prophylaxis (PrEP). Transcripts of qualitative data were coded to identify common themes related to engagement in HIV prevention. Results: Among 201 BLTW, 56% tested HIV-positive and 87% had heard of PrEP. Only 18% who had heard of PrEP had ever taken it. Of the 72 self-reported HIV-negative or status-unknown BLTW who had never taken PrEP, 75% were willing to take it. In multivariable analyses, history of exchange sex was associated with willingness to take PrEP, whereas greater HIV knowledge and transgender pride were associated with lower likelihood of willingness to take PrEP. Concern about drug interactions with hormone therapy was the most frequently reported barrier to PrEP uptake. Conclusions: Noting the disconnect between PrEP willingness and uptake among BLTW, HIV prevention programs could bridge this gap by responding to identified access barriers and incorporating community-derived strategies. Abstract : Supplemental Digital Content is Available in the Text.